Transdisciplinarity of vulvovaginal candidiasis from a social-environmental education perspective - Moreira, Paulo de Xavier Castro; Furtado, Haryne Lizandrey Azevedo; Mendes, Thayariane Lira; Silva, Ângela Nascimento da; Holanda, Rodrigo Assunção; Santos, Julliana Ribeiro Alves (Ciência e Natura, 2018)
Vulvovaginal candidiasis stems from the imbalance between the fungus, woman, and environment. This study aimed to describe the genital infection in an ecological vision to identify the risk factors and socio-environmental prophylactic education measures. This descriptive study employed the qualitative and bibliographical methods used in selected scientific articles. The descriptors used were biomedical model, ecological triad, natural history of the disease, systemic model, vaginal ecosystem, and women's disorders. The holistic approach broadens the knowledge of pathogenesis, characterizes risk factors, and identifies the links in the chain of events where prophylactic measures may be applied.